Conflict in Myanmar : war, politics, religion - Farelly, Nicholas; Cheesman, Nick, editor; Australian National University (Singapore : ISEAS-Yusof Ishak Institute, 2016)
Papers originally presented to the Myanmar/Burma Update Conference 2015 held at the Australian National University, Canberra, from 5 to 6 June 2015
Keywords: Burma -- Politics and government -- 21st century; Civil war -- Burma; Ethnic conflict -- Burma; Religion and politics -- Burma; Social conflict -- Burma